Stellar winds in massive X-ray binaries - Kretschmar, P; Martínez-Núñez, S; Bozzo, E; Oskinova, L; Puls, J; Sidoli, L; Sundqvist, J; Blay, P; Falanga, M; Fürst, F; Gímenez-García, A; Kreykenbohm, I; et al. (Cambridge University Press, 2017)
Strong winds from massive stars are a topic of interest to a wide range of astrophysical fields. In High-Mass X-ray Binaries the presence of an accreting compact object on the one side allows to infer wind parameters from studies of the varying properties of the emitted X-rays; but on the other side the accretor's gravity and ionizing radiation can strongly influence the wind flow. Based on a collaborative effort of astronomers both from the stellar wind and the X-ray community, this presentation attempts to review our current state of knowledge and indicate avenues for future progress.